Typology Towards Attempts to Interpret the Qur'an with As-Sunnah - Khairunnas Jamal; Ilyas Husti; Mochammad Novendri S (UM Purwokerto Press, 2023)
This study discusses the typology of attempts to interpret the Qur'an with as-Sunnah. In avoiding distortions and errors in interpretation, the most important thing to note is the source of an interpretation. Scholars argue that historical sources are the main ones, in particular the description of verses from the Qur'an with other verses and information sourced from the Prophet pbuh. So this paper examines the views and opinions of scholars in summing up patterns in interpreting the Qur'an with as-Sunnah. This research is library research and the methodology used in this research is descriptive research. The results of the discussion state that the form of interpretation of the Prophet Muhammad pbuh cannot be separated from the function of the sunnah itself as an explanatory. Sometimes the sunnah corroborates what the Qur'an says, other times the sunnah puts restrictions on the widely meaning pronunciation, sometimes also the sunnah details what is still common. The Prophet pbuh in interpreting verses sometimes begins by reciting the verses first then interpreting them or vice versa. In addition, there is also a form of interpretation of the Messenger of Allah pbuh by justifying what the friend misunderstood regarding the meaning of a verse or recitation in a verse.